2022
DOI: 10.3390/ijms23116127
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Changes in Actin Dynamics and Cell Motility as Early Responses of Cultured Mammalian Cells to Altered Gravitational Vector

Abstract: Cultured mammalian cells have been shown to respond to microgravity (μG), but the molecular mechanism is still unknown. The study we report here is focused on molecular and cellular events that occur within a short period of time, which may be related to gravity sensing by cells. Our assumption is that the gravity-sensing mechanism is activated as soon as cells are exposed to any new gravitational environment. To study the molecular events, we exposed cells to simulated μG (SμG) for 15 min, 30 min, 1 h, 2 h, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 74 publications
0
5
1
Order By: Relevance
“…Therefore, remodeling of cytoskeletal systems induced by the cell inversion against the gravity vector is necessary for safe nuclear translocation. Contrary to a previous report, another report observed cytoskeletal remodeling within a faster time frame (10 min) for single cells; this report revealed a transient reduction in actin stress fiber formation with a considerable increase in lamellipodia formation, followed by the complete loss of such changes within one or two hours [ 6 ]. Therefore, the cellular response to gravity is time-dependent; the transient effect shows lower actin stress fibers, whereas the adaptive effect shows higher actin stress fibers.…”
Section: Introductioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Therefore, remodeling of cytoskeletal systems induced by the cell inversion against the gravity vector is necessary for safe nuclear translocation. Contrary to a previous report, another report observed cytoskeletal remodeling within a faster time frame (10 min) for single cells; this report revealed a transient reduction in actin stress fiber formation with a considerable increase in lamellipodia formation, followed by the complete loss of such changes within one or two hours [ 6 ]. Therefore, the cellular response to gravity is time-dependent; the transient effect shows lower actin stress fibers, whereas the adaptive effect shows higher actin stress fibers.…”
Section: Introductioncontrasting
confidence: 58%
“…However, there might be a difference between the intrinsic migration velocity for single cells compared to cells in a group, especially when there are significant alterations in the biological functions of cells in groups compared to single cells, such as cellular adhesion, migration persistence [ 18 ], and drug sensitivity [ 19 , 20 ]. In contrast, Ju et al recently reported that upon inversion against gravity, single cells showed enhanced motility [ 6 ], which could be due to the intrinsic difference between the various cell lines or the difference between the substrates used for cell culture. Next, we examined whether the proliferation ratio was affected by the gravity vector, and the proliferation ratio was calculated by counting the number of cells just before the cluster expansion (0 h) and at 14 h after expansion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The human follicular thyroid carcinoma FTC-133 cell line (passages 8-18) was purchased from Sigma-Aldrich (St. Louis, MO, USA). The MCF-7 mammary carcinoma cells (passages 5-9) and PC-3 prostate carcinoma cells (passages [36][37][38][39][40] were purchased from ATCC (Manassas, VA, USA). The Calu-3 lung carcinoma cell line (passage 19) was a kind gift from Prof. Heike Walles, the University of Magdeburg.…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%